PENGARUH FOSFIN (PH3) TERHADAP MORTALITAS HAMA GUDANG Sitophilus oryzae L. PADA KOMODITAS GANDUM - Sarah Zulfiyah Febrianti; Suharto Suharto (Universitas Trilogi, 2019)
ABSTRACTWheat (Triticum spp.) is one of the commodities cereals are consumed by people in Indonesia. Indonesia climate conditions that are less in accordance with the growth and development of wheat crops affect food security of Indonesia. The imports of wheat Indonesia tend to increase from over the years. In the process, Sitophilus oryzae Linnaeus which is major insect pest of grain so that it causes damage and decrease of quality of grain. Therefore, effective control measures of this insect pest by quarantine officers are important. Phosphine solid formulations are expected to control pests S. oryzae effectively. The objectives of this study were to determine the dosage and exposure time which will were effectively kill S. oryzae on wheat commodities. S. oryzae on wheat was exposed to phosphine at 3 dosage (0.5 gr/m3, 1 gr/m3, and 1.5 gr/m3) and exposure times (6, 12, 18 and 24 hours). Moreover, mortality test of adult insect and adult insect of F1 offspring. Results showed that application of phosphine at dosage of 0.5 gr/m3, 1 gr/m3 and 1.5 gr/m3 with exposure time 18 and 24 hours completely killed 100% mortality adult insect of S. oryzae on wheat commodities. Dosage 1.5 gr/m3 with exposure time 24 hours show the average adult insect of F1 offspring as much as one tail. Keywords: Sitophilus oryzae L., Phosphine (PH3), Wheat